2021
DOI: 10.3389/fmed.2021.637246
|View full text |Cite
|
Sign up to set email alerts
|

Compare the Effect of Inhaled Corticosteroids and Systemic Corticosteroids on Sputum Microbiome of AECOPD

Abstract: Background: To observe the effects of inhaled corticosteroids (ICS) and systemic corticosteroids (SCS) on the sputum microbiology of patients with AECOPD.Methods: The 16S rRNA sequencing results for sputum samples from 36 admitted AECOPD patients were analyzed using ICS or SCS on the basis of standard treatment; sputum samples were collected before and after treatment for 1 day, 7, and 14 days.Results: After 7 days of SCS treatment, the bacterial abundance of Sorangium, Acidibacter, and Fretibacterium decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…In our study, the most dominant phylum in sputum samples of AECOPD patients was Proteobacteria, which was consistent with the previous reports that the occurrence of AECOPD was related to the reduction in microbiome diversity and increased proportion of Proteobacteria [ 25 , 26 ]. Proteobacteria and its members such as Haemophilus were associated with the onset of AECOPD [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the most dominant phylum in sputum samples of AECOPD patients was Proteobacteria, which was consistent with the previous reports that the occurrence of AECOPD was related to the reduction in microbiome diversity and increased proportion of Proteobacteria [ 25 , 26 ]. Proteobacteria and its members such as Haemophilus were associated with the onset of AECOPD [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…Qi et al [25] however reports no significant differences in alpha diversity between eosinophilic and noneosinophilic AECOPD before treatment. An increased microbiome diversity is observed seven days post combined corticosteroid and antibiotic treatment, independent of whether oral or ICS are used [25,26]. The differences observed are likely due to sample collection (i.e.…”
Section: Key Pointsmentioning
confidence: 98%
“…The five most prevalent phyla in sputum samples from patients with COPD during exacerbations are Firmicutes, Actinobacteria, Bacteroidetes, Proteobacteria, and Fusobacteria [ 12 , 33 , 57 ], while in the fecal samples of mice, the most prevalent phyla are Firmicutes, Bacteroidetes, Proteobacteria, and TM7 [ 5 ]. The most dominant genera in sputum samples during acute exacerbations of COPD are Streptococcus , which is the most prevalent, Neisseria , Porphyromonas , Haemophilus , Veillonella , Prevotella , Rothia , Pseudomonas , Staphylococcus , Proteus , and Moraxella [ 12 , 19 , 33 , 57 , 58 , 59 ]. Studies have shown that reduced microbial diversity is associated with COPD exacerbation events [ 19 , 31 , 33 , 57 , 59 ].…”
Section: The Relation Between Microbiomes and Copd Exacerbationsmentioning
confidence: 99%
“…The most dominant genera in sputum samples during acute exacerbations of COPD are Streptococcus , which is the most prevalent, Neisseria , Porphyromonas , Haemophilus , Veillonella , Prevotella , Rothia , Pseudomonas , Staphylococcus , Proteus , and Moraxella [ 12 , 19 , 33 , 57 , 58 , 59 ]. Studies have shown that reduced microbial diversity is associated with COPD exacerbation events [ 19 , 31 , 33 , 57 , 59 ].…”
Section: The Relation Between Microbiomes and Copd Exacerbationsmentioning
confidence: 99%
See 1 more Smart Citation